Three strong women: from care to university - Ian Milligan (Scottish Journal of Residential Child Care)
Poor educational 'outcomes' of looked after children have been a matter of increasing concern. This article explores some of the factors that might make for educational success by looking at the experiences of three young women who have been in care in Scotland and who have since progressed to university. By exploring these three stories, it is hoped that practitioners and researchers will gain a helpful insight into the crucial factors for them as individuals.